Insurance Accounting Research: Themes, Gaps, and Global Directions - Kumar, Hemant; Rastogi, Dr. Ranjul (International Journal of Accounting and Economics Studies, 2025)
Purpose: This study maps the intellectual structure and evolving themes of insurance accounting ‎by integrating a systematic literature review with bibliometric analysis. The aim is to identify ‎dominant research clusters, surface thematic and regional gaps, and inform future academic inquiry ‎and standard-setting dialogue.‎Research Problem: Despite insurance accounting’s transformative stage, the literature remains ‎fragmented across technical design, institutional dynamics, and regulatory practice. A consolidated ‎view of core themes, knowledge gaps, and intellectual linkages is needed to advance cumulative ‎scholarship and support evidence-based standard-setting.‎Design/Methodology/Approach: A corpus of 142 peer-reviewed articles (2005–August 2025) ‎was systematically reviewed. Bibliometric techniques implemented in Bibliometrix/Biblioshiny ‎were used for citation and co-authorship mapping, keyword co-occurrence, cluster identification, ‎and geographic analysis. The mixed-method design combines thematic synthesis with quantitative ‎network metrics to assess research patterns and influence.‎Findings: Five interlinked themes dominate: liability measurement, fulfilment cash flows and ‎discounting, disclosure and communication, stakeholder perspectives and governance, and ‎implications for primary financial statements. Publications accelerate from 2020, yet gaps persist in ‎post-implementation evidence, triangulated designs, and coverage of emerging economies. ‎Practical Implications: The mapping provides a prioritised agenda for scholars, regulators, and ‎practitioners: expand longitudinal and mixed-methods research; evaluate transition choices and ‎contractual service margin effects; strengthen disclosure specificity and KPI consistency; and build ‎capacity in under-represented jurisdictions to support harmonised implementation.‎Originality/Value: To the best of our knowledge, this is the first study to combine full bibliometric ‎mapping with a systematic review to comprehensively chart post-insurance accounting reforms.
Keywords: Insurance Accounting; IFRS 4; IFRS 17; Bibliometric Analysis; Systematic Literature Review; ‎Disclosure; Liability Valuation